PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SEKOLAH DASAR - Hazmiwati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The background of this research is still low absorption of second grade students in science subject matter. The purpose of this study is to improve the learning outcomes of Science Class II SDN 008 Bumi Ayu through STAD type cooperative learning model. This research took place in class II SDN 008 Bumi Ayu with the number of subjects as many as 20 people consisting of 9 female students and 11 male students. This research is a classroom action research conducted in two cycles. Based on the percentage results obtained by individual and classical completeness by applying STAD type cooperative learning model, before the action of 20% is complete, in the first cycle increased 55% and in the second cycle increased by 90%. Increased learning outcomes on baseline score 64 increased to 76.75 in cycle I, with an increase of 19.92%. In cycle II the average of student learning outcomes again increased to 84.5 with the increase that occurred from cycle I to cycle II is equal to 10.1%.